Identificação dos locais de interesse geomorfológico do Rio Claro Triângulo Mineiro - Luz Netto, Fausto Miguel da (2015)
Researches into Geomorphologic Heritage, developed intensively in Europe, are highly rated and well developed, with applicability in several areas of knowledge, especially in Geoscience, and inserted into people’s everyday life, mainly for those specialized in related areas to this theme. In Brazil, this theme is considered relatively new and in Triângulo Mineiro region there are few papers that approached and/or develop researches into Geomorphologic Heritage. In this research, the approach of Geomorphometry is used as a science of contribution to the geomorphologic analysis and the possibility of facilitating the identification of places of geomorphologic interest. The Rio Claro riverbed features two different behaviors. In the upper-middle course it is possible to observe its features in consonance with tablelands slightly concave and depressed, and from the lithologic contact between the Formations Marília and Serra Geral it occurs the fluvial dynamic alteration, with great volume of water and the formation of various geomorphologic features, such as rapids, waterfalls and canyons. To achieve the proposed goals, this study is based on bibliographic research of the theme, study area, field work, cartographic data processing and analysis and considerations presented along this dissertation. Through the application of this methodology, five geomorphologic places of interest have been found, all featured, with scientific, aesthetic and tourist value. In Geomorphometry the variables proposed and analyzed are important for facilitating the geomorphologic and landscape comprehension of the study area, however there were not observed substantial contributions to the identification of Geomorphologic Heritages. We conclude that this study present a recent approach, that contributes to a new perspective to landscape abiotic aspects, which are analyzed in many academic and technical studies in a simple-minded way, even these aspects being in the same level of importance in the biotic environment.